Implementation of new agricultural models in Colombia (2013)
Over time, the agriculture has been a strategic importance, because it has led to the development and evolution of rural areas, after the above has led to propose new theories that create strategies and policies that strengthen the agriculture, so is necessary for developing of the countries such as Colombia, define new models in which the farmer begins to use all the resources efficiently through the training, land reforms in Colombia only have consisted in redistributing land, these haven’t focused on access to training and education, so it has had a negative impact on the quality of life of beneficiaries of these reforms. Key words: agrarian reform, agriculture policy, new theories, land redistribution, training